District-wise first order seismic loss estimation to the brick masonry buildings, in the states: Uttar Pradesh, Uttarakhand, Punjab and Tamil Nadu - Balasubramanian, S.R.; Rao, K. Balaji; Vasuki, P.; Anoop, M.B.; Joseph, J. Daniel Ronald; Iyer, Nagesh R. (Journal of Structural Engineering, 2025)
In this paper a simple methodology for estimating expected, regional seismic loss to the brick masonry buildings has been presented. The seismic loss estimation has been carried out for the districts of four states in India. This methodology integrates the information from various sources in a systematic way. The seismic loss values obtained would be useful in prioritising/mobilising the resources meant for earthquake risk management/relief operations etc. It is noted that the methodology proposed can include any improvements in the knowledge.